Simulating Sea‐Ice Deformation in Viscous‐Plastic Sea‐Ice Models With CD‐Grids - C. Mehlmann; G. Capodaglio; S. Danilov (Journal of Advances in Modeling Earth Systems, 2023)
Abstract Linear kinematic features (LKFs) are found everywhere in the Arctic sea‐ice cover. They are strongly localized deformations often associated with the formation of leads and pressure ridges. In viscous‐plastic (VP) sea‐ice models, the simulation of LKFs depends on several factors such as the grid resolution, the numerical solver convergence, and the placement of the variables on the mesh. In this study, we compare two recently proposed discretization with a CD‐grid placement with respect to their ability to reproduce LKFs. The first (CD1) is based on a nonconforming finite element discretization, whereas the second (CD2) uses a conforming subgrid discretization. To analyze their resolution properties, we evaluate runs from different models (e.g., FESOM, MPAS) on a benchmark problem using quadrilateral, hexagonal and triangular meshes. Our findings show that the CD1 setup simulates more deformation structure than the CD2 setup. This highlights the importance of the type of spatial discretization for the simulation of LKFs. Due to the higher number of degrees of freedom, both CD‐grids resolve more LKFs than traditional A, B, and C‐grids at fixed mesh level. This is an advantage of the CD‐grid approach, as high spatial mesh resolution is needed in VP sea‐ice models to simulate LKFs.